Role of Bronchoalveolar Lavage (BAL) Gene Xpert in Diagnosis of PTB in Sputum Smear Negative Patients - Alom, KM Monjurul; Ali, Mirza Mohammad Idris; Mahmud, Md Jakaria; Ahmed, Md Mohiuddin (Community Based Medical Journal, 2023)
The aim of this study was to assess the diagnostic efficacy of Xpert MTB/RIF assay in bronchoalveolar lavage (BAL) in the diagnosis of pulmonary tuberculosis in sputum-smear negative patients. This observational case series study was conducted in a tertiary base institute of Bangladesh from July 2017 to June 2019. All patients with suspected pulmonary tuberculosis who were sputum-smear negative, irrespective of age and gender were included in this study. BAL fluid thus obtained and examined the smear for acid fast bacilli (AFB) and Xpert MTB/RIF assay. The sensitivity, specificity and accuracy values were calculated for smear AFB and Xpert MTB/RIF assay. Xpert MTB/RIF was identified 33 (36.7%) of 90 patients on bronchoalveolar lavage fluid in the final analysis. AFB Fluid culture was positive in 28 (31.2%) cases. The sensitivity and specificity of Xpert MTB/RIF assay was 85.7%, and 85.5% respectively. The positive likelihood ratio was 5.90, and the negative likelihood ratio was 0.167. The accuracy was 85.56%. Xpert MTB/RIF on BAL fluid can be recommended as a fruitful diagnostic tool for mycobacterium pulmonary tuberculosis especially in sputum smear negative, and culture negative patients. CBMJ 2023 January: Vol. 12 No. 01 P: 60-66